Estilos parentales y conductas autolesivas en adolescentes - Ana Lizbeth, Yambay Cajamarca (2021)
ABSTRACT Parental styles can be classified into several types, including negligent, authoritarian, democratic and permissive, which may or may not interfere with self-injurious behaviors in adolescents, among these behaviors, the most common are cuts in different parts of the body, scratches, burns on the skin, avoid wound healing, among others. The objective of this research is to analyze parenting styles and self-injurious behaviors in adolescents. For this, a bibliographic review study was carried out, with a quantitative and qualitative approach, which is made up of a population of 84 documents published in several indexed journals, between the years 2015-2020. Whose sample belonging to 32 writings that include scientific articles, graduation thesis works, master's and doctorate theses, for this, the bibliographic review matrix was used that allowed the selection of study articles, since the quartile and the factor of the scientific journals that were entered into the Scimago Journal Ranking was assessed, it allows evidencing these factors, in the same way the ACC greater than 1.50 was evaluated, since this reflects the quality of the article. It was possible to analyze parenting styles and self-injurious behaviors in the study population, in addition to establishing some strategies for the reduction of self-injurious behaviors, among which, positive parenting in parents, psychological therapy such as behavioral dialectics, group intervention of emotional, cognitive and behavioral intervention and the problem-solving therapy stand out. Keywords: self-harm, adolescents, behavior, parenting styles. Reviewed by: Mgs. Geovanny Armas Pesántez ENGLISH PROFESSOR C.C. 0602773301